2014
DOI: 10.1136/oemed-2014-102095
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of livestock-associated antibiotic-resistantStaphylococcus aureusamong industrial hog operation workers in North Carolina over 14 days

Abstract: ObjectivesThis study aimed to evaluate the persistence of nasal carriage of Staphylococcus aureus, methicillin-resistant S. aureus and multidrug-resistant S. aureus over 14 days of follow-up among industrial hog operation workers in North Carolina.MethodsWorkers anticipating at least 24 h away from work were enrolled June–August 2012. Participants self-collected a nasal swab and completed a study journal on the evening of day 1, and each morning and evening on days 2–7 and 14 of the study. S. aureus isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 37 publications
6
64
1
Order By: Relevance
“…Other comparative-genomics studies of S. aureus CC398 also indicated that the best genetic markers of human-associated CC398 were IEC genes (scn and chp), while the best genetic marker of the livestock-associated CC398 was tet(M) (43,44). In addition, a study of industrial hog operation workers in the United States reported that 82% of livestock-associated S. aureus isolates demonstrated resistance to tetracycline and that livestock-associated CC398 was not detected among scn-positive isolates (45). These findings highlight the need for further whole-genome analysis and comparative-genomics analysis to better identify genetic markers of livestock-to-human transmission of S. aureus CC9, which has been referred to as the most pandemic livestock-associated clone in Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other comparative-genomics studies of S. aureus CC398 also indicated that the best genetic markers of human-associated CC398 were IEC genes (scn and chp), while the best genetic marker of the livestock-associated CC398 was tet(M) (43,44). In addition, a study of industrial hog operation workers in the United States reported that 82% of livestock-associated S. aureus isolates demonstrated resistance to tetracycline and that livestock-associated CC398 was not detected among scn-positive isolates (45). These findings highlight the need for further whole-genome analysis and comparative-genomics analysis to better identify genetic markers of livestock-to-human transmission of S. aureus CC9, which has been referred to as the most pandemic livestock-associated clone in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a low incidence of the IEC genes in cattle isolates of S. aureus (40,41). Recent work has demonstrated that absence of the scn gene may aid in the differentiation of the animal origin of S. aureus carried by humans exposed to livestock (42)(43)(44)(45). Recent comparative-genomics studies of human versus animal isolates have revealed that animal-related isolates are significantly less likely to possess the IEC genes (chp, scn, and sak) carried on ␤-hemolysin-converting bacteriophages (42).…”
Section: Discussionmentioning
confidence: 99%
“…Strains of S. aureus with genetic and phenotypic markers of livestock adaptation have been identified in many countries, including France (Armand-Lefevre et al, 2005), the Netherlands (Huijsdens et al, 2006;Van den Broek et al, 2009), Belgium (Denis et al, 2009), Canada (Khanna et al, 2008), and the United States (Nadimpalli et al, 2014;Rinsky et al, 2013;Smith et al, 2013;Smith et al, 2009). These livestock-associated strains of S. aureus have also emerged in the community in areas with a high density of pig farming (Van Cleef et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Although ST398 is identified commonly in pigs and farming environments in North America [73,[92][93][94][125][126][127][128][129][130][131][132][133], there appears to be a greater diversity of molecular types found on North American farms compared with those in Europe, where ST398 remains the dominant or sole strain of MRSA identified. One study in Michigan found no ST398 present in the pigs sampled [134], whereas the bulk of studies have found a mix of Bhuman^types (such as ST8 and ST5) in conjunction with ST398.…”
Section: Evolution Of La-mrsa In North Americamentioning
confidence: 99%